Crescimento inicial de teca e produtividade de soja sob diferentes adubações em sistema agrossilvicultural - Abreu, Sandro Alex Helrigel (2016)
The Agroforestry Systems (SAF’s) are models of agricultural exploration that using forest species intercropped with agricultural crops and/or forage with or without animal presence. They have been widely disseminated therefore contribute to the sustainability of the agriculture. This study was developed from an experiment conducted in agrossilvicultural system during the period 2013-2015, the Federal University of Goiás, city of Goiania, GO. The objective of this study was to evaluate the chemical properties of soil, development and productivity of plant components in system integration (Teca and soybean), using different fertilization soil and cropping systems. The experimental design was a randomized block with four replications, in arrangement factorial 4 x 2, consists of four types of fertilization: no application (control); mineral fertilization; application of cattle manure and application of sewage sludge in two cropping systems: single Teca and Teca intercropped with soybeans. The chemical properties of the soil were favored by the application of sewage sludge. There not increase in levels of heavy metals in soil by use of organic waste. The productivity of soybean fertilized with sewage sludge did not differ of the mineral fertilizer, being higher other fertilization. The initial performance of Teca in single cropping was favored by the application of both organic waste. However, when intercropped with soybean, sewage sludge application resulted in higher values of height and diameter at breast height (DBH). The canopy of the tree component of the system was not influenced by the type of fertilizer used, keeping constant the light rate in the different fertilization. The use of sewage sludge is favorable both for the initial development of Teca as plants for soybean yield, being recommended in agrossilviculturals systems.